2018
DOI: 10.1021/acs.est.8b05304
|View full text |Cite
|
Sign up to set email alerts
|

Potential Toxicity of Complex Mixtures in Surface Waters from a Nationwide Survey of United States Streams: Identifying in Vitro Bioactivities and Causative Chemicals

Abstract: While chemical analysis of contaminant mixtures remains an essential component of environmental monitoring, bioactivity-based assessments using in vitro systems increasingly are used in the detection of biological effects. Historically, in vitro assessments focused on a few biological pathways, for example, aryl hydrocarbon receptor (AhR) or estrogen receptor (ER) activities. High-throughput screening (HTS) technologies have greatly increased the number of biological targets and processes that can be rapidly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 53 publications
5
99
0
Order By: Relevance
“…In that study, the in vitro HTP Attagene system described in Section 5 of this paper was used to evaluate pathwaybased bioactivities of 38 surface water samples from around the US, which also had been subjected to extensive instrumental analytical characterization. Blackwell et al (2018)…”
Section: Accepted Articlementioning
confidence: 99%
“…In that study, the in vitro HTP Attagene system described in Section 5 of this paper was used to evaluate pathwaybased bioactivities of 38 surface water samples from around the US, which also had been subjected to extensive instrumental analytical characterization. Blackwell et al (2018)…”
Section: Accepted Articlementioning
confidence: 99%
“…Many PW treatment studies have focused on a "treat for use" approach. As such, assay trigger values should be defined for different downstream users (Blackwell et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…endocrine disruption, mutagenicity, etc.) are elevated in surface water downstream of partially treated industrial discharges and wastewater treatment plant (WWTP) effluents (Ohe et al, 2004;Blackwell et al, 2019). Additionally, studies have demonstrated both acute and chronic toxicity in organisms exposed to PW and its constituents (Blewett et al, 2017;Cozzarelli et al, 2017;Folkerts et al, 2017aFolkerts et al, , 2017bHe et al, 2017aHe et al, , 2017bKassotis et al, 2014Kassotis et al, , 2015Kassotis et al, , 2016a.…”
Section: Introductionmentioning
confidence: 99%
“…The use of in vitro bioassays for environmental monitoring is a rapidly expanding field of research [15][16][17][18][19][20][21][22][23][24][25]. While the bioassays cannot discriminate between the toxic effects of two or more compounds that are present in the same sample, the great strength with bioassays is that they show the total toxicity exerted by a sampleregardless whether the toxicity is caused by a known anthropogenic compound, an unknown anthropogenic compound, a naturally occurring compound, or a combination of these [6,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…While the bioassays cannot discriminate between the toxic effects of two or more compounds that are present in the same sample, the great strength with bioassays is that they show the total toxicity exerted by a sampleregardless whether the toxicity is caused by a known anthropogenic compound, an unknown anthropogenic compound, a naturally occurring compound, or a combination of these [6,26,27]. The contribution of micropollutants to the bioactivity in surface water affected by wastewater has been evaluated in recent studies, showing that the major part of the bioactivities cannot be explained by target compounds [16,22,[28][29][30][31][32]. Bioanalytical studies focusing on pesticides in water from agricultural areas are scarce.…”
Section: Introductionmentioning
confidence: 99%